Client and therapist agreement in moment‐to‐moment helpfulness ratings in psychotherapy: A microprocess approach. Issue 1 (17th July 2020) - Penix, Elizabeth A.; Swift, Joshua K.; Russell, Kelley A.; Trusty, Wilson T.
Abstract: Method: Clients ( n  = 16; M age  = 32.88 years; 81% female) and their therapists ( n  = 10; 80% female) from a training clinic provided moment‐to‐moment ratings while reviewing a video recording of a recent session. West and Kenny's Truth‐and‐Bias (T&B) model was used to examine agreement in ratings. Multilevel modeling was used to evaluate the agreement‐alliance association while controlling for sessions completed. Results: Consistent with the T&B model, client–therapist ratings were temporally congruent and were not discrepant overall. Greater congruence and smaller discrepancies were linked with stronger alliances. Conclusions: The within‐session and between‐dyad variability in helpfulness ratings highlight the utility of moment‐to‐moment rating methods. Findings suggest that therapists should attune to client perceptions on a within‐session level and attunement may be a target for enhancing the alliance.